Classroom Peer Relationships and Behavioral Engagement in Elementary School: The Role of Social Network Equity. Issue 3 (1st October 2013) - Cappella, Elise; Kim, Ha Yeon; Neal, Jennifer W.; Jackson, Daisy R.
Abstract: Applying social capital and systems theories of social processes, we examine the role of the classroom peer context in the behavioral engagement of low‐income students ( N = 80) in urban elementary school classrooms ( N = 22). Systematic child observations were conducted to assess behavioral engagement among second to fifth graders in the fall and spring of the same school year. Classroom observations, teacher and child questionnaires, and social network data were collected in the fall. Confirming prior research, results from multilevel models indicate that students with more behavioral difficulties or less academic motivation in the fall were less behaviorally engaged in the spring. Extending prior research, classrooms with more equitably distributed and interconnected social ties—social network equity—had more behaviorally engaged students in the spring, especially in classrooms with higher levels of observed organization (i.e., effective management of behavior, time, and attention). Moreover, social network equity attenuated the negative relation between student behavioral difficulties and behavioral engagement, suggesting that students with behavioral difficulties were less disengaged in classrooms with more equitably distributed and interconnected social ties. Findings illuminate the need to consider classroom peer contexts in future research and intervention focused on the behavioral engagement of students in urban elementary schools.